2017
DOI: 10.15406/ppij.2017.05.00142
|View full text |Cite
|
Sign up to set email alerts
|

Production of Purified MRSAcin from Local Clinical Strain of Methicillin-Resistant Staphylococcus aureus and its Applicability as Antimicrobial

Abstract: Confirmation of S. Aureus:The samples collected on mannitol salt broth media were incubated at 37°C for 24h and then inoculated onto mannitol salt agar media and incubated at 37°C for 24h. Selected isolates with colony morphology, Gram stain reactions and biochemical characteristics (i.e., Coagulase, Catalase reagent, Oxidase reagent).Confirmation of MRSA and antibiotic resistance testing: All isolates of S. aureus that demonstrated any level of Oxacillin (Methicillin) and Cefoxitin (FOX) resistance. All cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…When using of antibiotic sensitivity test, 40 (69%) S. aureus isolates exhibited resistance to gentamicin. This result was approximately parallel with Ahmed and Al Mossaw [30] who showed that 60% of isolates were gentamicin resistant. In a local study, in Duhok by Abdullah [31] showed that 59 (39.07%) of S. aureus isolates from UTI were gentamicinresistant.…”
Section: Discussionsupporting
confidence: 80%
“…When using of antibiotic sensitivity test, 40 (69%) S. aureus isolates exhibited resistance to gentamicin. This result was approximately parallel with Ahmed and Al Mossaw [30] who showed that 60% of isolates were gentamicin resistant. In a local study, in Duhok by Abdullah [31] showed that 59 (39.07%) of S. aureus isolates from UTI were gentamicinresistant.…”
Section: Discussionsupporting
confidence: 80%